The Effectiveness of the Use of Technology in Patient-Centred Care for Counterfeit Drug Control - Amusa, Morufu (2023)
Counterfeit drugs impose risk to human life and properties. Many organizations globally are involved in counterfeit drugs control with focusing on pharmaceutical production and supply chain, while less or rare efforts are invested at terminal intervention by the end users. This study focused on end users in the six geopolitical zones in Nigeria. A prototype Information System (IS) developed using Short Message Services of Mobile Telecommunication System. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was adopted with new two relevant variables namely, Zero-Cost and Health Condition introduced to fit the context of this study. UTAUT employed to investigate the key factors affecting the users’ intention to use the Patient-Centred System for Counterfeit Drug Control (PACSCDC) using Questionnaires Survey. Two groups involved in the investigation on fake drugs awareness and factors influencing users’ intention using the system and its effectiveness. Random sampling technique adopted for participant, 1391, 2593 respectively, the reliability of data collected and survey achieved with Cronbach’s Alpha value of 0.713 and 0.949 respectively. Descriptive and inferential analytical methods employed via the Statistical Package for the Social Sciences (SPSS). Hypertext Pre-processor (PHP) used as scripting language. Study discovered the need of users to have awareness on counterfeit drugs, to have tailored information system and factors affecting intention of user to use the system revealed. The novelty of this work resides in the design of a system that works on unsophisticated mobile telephones, simplicity communication with users, and assisting in patient-drug education beside detecting fake drugs. This work contributes theoretically & practically to the knowledge.